RELATIONSHIP BETWEEN PRE-SERVICE MATHEMATICS TEACHERS' TEACHING AND LEARNING BELIEFS AND THEIR PRACTICES - (:unkn) unknown (INT GRP PSYCHOL MATH EDUC, 2006)
The purpose of this study was to determine pre-service mathematics teachers' teaching and learning beliefs and examine the relationship between their belief's and practices. Qualitative and quantitative research methods were designed for this study. Survey, semi-structured interviews, observations, and pre-service teachers' written documents such as school practice portfolios were used to collect the data. Under the developed theoretical framework it was found that some of the pre-service mathematics teachers beliefs were consistent with their practices; while some of them presented different practices from their beliefs.